INTERCULTURAL COMMUNICATION AS A THEORETICAL AND PRACTICAL SCIENCE - Paziljanova Zulfiya Sabirjanovna (Galaxy International Interdisciplinary Research Journal, 2022)
The theory of intercultural communication is a science that sheds light on the process of intercultural communication, the conditions for its implementation, possible difficulties and reasons for communication failures. This article examines the concept of intercultural communication, the main features of the theory of intercultural communication, interdisciplinary relations, the history of this discipline, the scope of knowledge application in the field of intercultural communication.